Bar el Chino (Buenos Aires, Argentina Vocacion S.R.L.)
Two filmmakers fall in love with each other and with Bar "El Chino", where tango is sung. Captivated, they work together on a documentary project about the Bar in an effort to capture the magic and essence of the place.
Executive producer : Mario Ezequiel Levit ; Producer : Mario Lion.
Cast : Boy Olmi, Jimena La Torre, Pasta Dioguardi, Nestor Sanchez, Lucas Santa Ana, Ernesto Larrese.
Keywords: Bar el Chino (Buenos Aires, Argentina).; Tangos -- Argentina; Music -- Argentina; Comedy -- Feature; Romance -- Feature